1991
DOI: 10.1042/bst0190858
|View full text |Cite
|
Sign up to set email alerts
|

Signal transduction in photoreceptors

Abstract: The biochemical role of the visual-pigment protein, rhodopsin, is reviewed, with reference to vertebrate rods and cones and the microvillar photoreceptors of invertebrates. New results are presented on the structure of squid rhodopsin, which possesses an extensive proline-rich repeat at its C-terminus, using negative-stain electron microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…103,104 Diminution of rhodopsin expression proportionally decreases the size of rod outer segment structures, while maintaining the same density of rhodopsin as in native discs, 98,105 whereas overexpression of rhodopsin results in enlargement of these structures that ultimately causes their instability. [105][106][107] Early work using biophysical approaches by Chabre 108 (Laboratoire de Biophysique Moléculaire et Cellulaire, Grenoble, France), Saibil 109 (Department of Biological Sciences and ISMB Birkbeck College, London, UK), and Cone, 110 and Poo 111 (Johns Hopkins University) suggested that rhodopsin is monomeric and moves rapidly within the discs. Such mobility was arguably required for high speed phototransduction.…”
Section: Rhodopsin Is Critical For the Organization Of Rod Outer Segmmentioning
confidence: 99%
“…103,104 Diminution of rhodopsin expression proportionally decreases the size of rod outer segment structures, while maintaining the same density of rhodopsin as in native discs, 98,105 whereas overexpression of rhodopsin results in enlargement of these structures that ultimately causes their instability. [105][106][107] Early work using biophysical approaches by Chabre 108 (Laboratoire de Biophysique Moléculaire et Cellulaire, Grenoble, France), Saibil 109 (Department of Biological Sciences and ISMB Birkbeck College, London, UK), and Cone, 110 and Poo 111 (Johns Hopkins University) suggested that rhodopsin is monomeric and moves rapidly within the discs. Such mobility was arguably required for high speed phototransduction.…”
Section: Rhodopsin Is Critical For the Organization Of Rod Outer Segmmentioning
confidence: 99%
“…5 and 6), a feedback pathway with Ca2+ as an inhibitor of rhodopsin-Gq activation is unlikely. Regarding receptor activation of the Gq, squid rhodopsin is homologous to other rhodopsins and to G-protein-coupled receptors, but has a proline-rich C-terminal extension [28,29]. This C-terminal tail is not present in Drosophila rhodopsin, and does not appear to play a role in G-protein activation or specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Os fotorreceptores são neurônios especializados responsáveis pelo início do processamento da informação visual na retina, capazes de converter energia luminosa em energia eletroquímica, por meio de uma série de cascatas bioquímicas. Tal processo inicia-se a partir da interação entre fótons e moléculas presentes em regiões específicas dos fotorreceptores Langmack & Saibil, 1991). Os fotorreceptores clássicos são encontrados na camada de fotorreceptores da retina externa dos vertebrados.…”
Section: Os Fotorreceptores E O Início Do Processamento Visualunclassified